Ageing Arsenals in Southeast Asia: Impact on Military Modernisation - Wu, Shang-su (2016)
Military modernisation in Southeast Asian countries has been viewed as an issue of military procurements threatening regional stability. Many regional armed forces face the challenge of managing a proper life cycle for their equipment, which in turn could influence regional stability.